Volume and Quality of Infrastructure and the Distribution of Income: An Empirical Investigation - Alberto Chong; César Calderón (Inter-American Development Bank, Research Department, 2001)
We provide evidence on the link between infrastructure development and the distribution of income for the period 1960-1995. To do this, we use several proxies such as roads, railways, telecommunications and energy measures. The approach is comprehensive as cross-country and panel methods are applied. In the latter case, we apply GMM dynamic panel methods in order to minimize for endogeneity problems. Both quantity of infrastructure and quality of infrastructure are negatively linked with income inequality. The quantitative link tends to be stronger in developing countries than the qualitative link. These findings hold when using different econometric methods and most infrastructure measures.
Keywords: 330; Infrastrukturpolitik; Einkommensverteilung; Welt